Determinants and consequences of share repurchases: Evidence from U.S. public firms - Md Minar Hossain; Umme Zinia Zahan Nodia; Falguni Rahman; Md Mehedi Hasan Antor; Mohammad Tahmid Ahmed; Farhana Akter Priya (Goodwood Publishing, 2025)
Purpose: This study investigates the underlying motivations behind share repurchases by U.S. companies and evaluates their impact on firm performance. It specifically explores financial conditions, managerial incentives, and market-related factors that drive buyback decisions, as well as the short- and long-term consequences for shareholders. Methodology/Approach: A quantitative, deductive approach is applied using data from publicly listed U.S. firms. Secondary data are sourced from Compustat, CRSP, ExecuComp, Bloomberg, and SEC filings. The analysis employs panel regressions, event-study methods, and multiple robustness checks conducted with statistical software such as Stata or R. Results/Findings: The findings indicate that free cash flow availability and perceived stock undervaluation are the most influential determinants of repurchases. Buyback announcements produce positive short-term market reactions, and firms demonstrate subsequent improvements in ROE and EPS. Nevertheless, share repurchases do not consistently enhance long-term abnormal stock returns. The results also show no significant reduction in investment, R&D, or employment, implying that buybacks are typically financed through excess liquidity. Conclusions: Share repurchases primarily function as a mechanism for capital allocation rather than a substitute for productive investment. While they generate short-term value for shareholders, their long-term effects tend to be neutral. Limitations: The study is restricted to U.S. firms and a specific time frame, and endogeneity concerns remain despite methodological controls. Contribution: This research advances understanding of buyback motives and outcomes, offering insights for managers, investors, and policymakers in evaluating repurchase strategies.